Implication of Structuralist and Generativist Theories in English Language Classrooms at Community Schools in Morang - Acharya, Tirtha Raj (Journal of Janta Multiple Campus, 2025)
This paper is concerned with the two linguistic theories: structuralism and generativism and their practical aspect in English language classrooms in the context of Urlabari, Morang. This paper deals with the theoretical bases of these theories, global trends, and their practice in teaching and learning from secondary teachers' perspectives and the issues related to theories of teaching and learning in the context of community schools. This study employed a survey design and explored the participants' experiences and practices in teaching English at community schools in Urlabari Municipality. Although teachers had an idea of these two theories, they prefer structuralist theories and follow the activities guided by them such as pattern practice, and rote learning and memorization rather than communicative activities such as pair work, group work, role play, information gap, and language exchange games. Also, it reflects that, unlike the communicative approach, structural approaches have been used as dominant methods of second or foreign language teaching in English classrooms.